2005
DOI: 10.1088/0957-4484/16/2/018
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of LaPO4 and CePO4 nanorods/nanowires

Abstract: LaPO(4) and CePO(4) nanorods/nanowires with controlled aspect ratios have been successfully synthesized using a hydrothermal microemulsion method under mild conditions. It has been shown that the obtained LaPO(4) has a monoclinic structure, while CePO(4) exists in the hexagonal structure. Uniform nanorods/nanowires with diameters of 20-60 nm and lengths ranging from several hundreds of nanometres to several micrometres were obtained. The aspect ratios of the obtained 1D nanostructures can be fine-tuned by simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 34 publications
5
45
0
Order By: Relevance
“…This indicated the exist of LaPO 4 shell. These phenomena have been reported by some group [25][26][27]. The CePO 4 had the similar crystal structure of monoclinic structure and close lattice constants compared with monoclinic LaPO 4 (JCPDS 32-0493, lattice constants: a = 6.836 Å, b = 7.076 Å, c = 6.509 Å).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This indicated the exist of LaPO 4 shell. These phenomena have been reported by some group [25][26][27]. The CePO 4 had the similar crystal structure of monoclinic structure and close lattice constants compared with monoclinic LaPO 4 (JCPDS 32-0493, lattice constants: a = 6.836 Å, b = 7.076 Å, c = 6.509 Å).…”
Section: Resultssupporting
confidence: 81%
“…6b). This indicates that the CePO 4 /LaPO 4 core/shell structure has been formed by completely being coated of the LaPO 4 shell on the CePO 4 core and the products are not mechanical mixtures of CePO 4 and LaPO 4 , which should have strong Ce 3d and La 3d peaks, according to the previous reports [25][26][27]. Our obtained CePO 4 /LaPO 4 core/shell structure had a shell thickness of about 5 nm, thus bringing about the weak Ce 3d peaks as compared to the La 3d peaks, due to the limitation of X-ray penetration.…”
Section: Resultssupporting
confidence: 63%
“…2c, d, it was also demonstrated that a higher pH condition made the particle size smaller drastically. From these results, one can conclude that the particle morphology of [15]. In the following sections, we focused on CePO 4 and (Ce 0.97 Sr 0.03 )PO 4 powders presented in Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Previous studies have already shown the micelles to be lens-shaped under these conditions. [24] In addition to electron microscopy, dynamic light scattering (DLS) was carried out to validate the particle size and size distribution of the nanomaterials subsequent to phase separation, centrifugation, and resuspension in DEG (Fig. 3).…”
Section: Full Papermentioning
confidence: 99%